Constipation in patients with comorbidity - E. A. Lyalyukova; E. N. Loginova (Лечащий Врач)
Elderly and senile patients, due to physiological reasons and comorbid pathology, have a high risk of constipation. The causes of constipation are more often nutritional factors and age-associated diseases and damage to the colon (diverticular disease, colon ischemia, rectocele, hemorrhoids, and others); metabolic, endocrine disorders and neurological diseases. Age-related anatomical, structural and functional changes in the digestive system contribute to the development of constipation in the elderly. In patients of «silver age», there was an increase in the length of the gastrointestinal tract, the progression of atrophic, sclerotic changes in the mucous and submucosa, a decrease in the number of secretory cells, replacement of muscle fibers with connective tissue, etc. All this contributes to the slowing down of transit through the gastrointestinal tract and the violation of the act of defecation. Elderly lifestyles can also contribute to constipation. The low fiber content in the diet, the use of mainly thermally processed food, the violation of the rhythm of the diet (eating 1-2 times a day) are one of the causes of constipation in the elderly, which is facilitated by difficulty in chewing due to dental problems. Colonoscopy is ordered for all elderly and senile patients with constipation, and the identification of «anxiety symptoms» should be carried out at each patient visit. Regardless of the cause of secondary constipation, all patients should take a number of non-pharmacological measures, including lifestyle changes, a diet with adequate fiber, and fluid intake. Physical therapies may include medical gymnastics, colon massage to stimulate bowel movement at specific times. If non-drug measures are ineffective, it is recommended to use osmotic laxatives, as well as agents that increase the volume of feces. Psyllium supplementation is recommended for treatment of chronic constipation in elderly patients due to its high efficacy and safety.